Proposal for the binding mode of the 23-mer inhibitory peptide to myostatin. (15th June 2021) - Asari, Tomo; Ikeyama, Hiroaki; Taguchi, Akihiro; Taniguchi, Atsuhiko; Hayashi, Yoshio; Takayama, Kentaro
Graphical abstract: Abstract: Inhibition of myostatin is a promising strategy for the treatment of amyotrophic disorders. Previously, we identified a minimum 23-mer peptide spanning positions 21–43 of a mouse myostatin precursor-derived prodomain and identified the nine key residues for effective myostatin inhibition through Ala scanning. We also reported the 23-mer peptides that show the propensity to form an α -helical structure around positions 32–36. Here, based on these findings, we conducted a docking simulation of a peptide-myostatin interaction. The results showed that by α -helix restraint docking of the 30–41 main chain, we obtained a proposed binding mode in which all nine of the key residues interact with myostatin. By analyzing the binding mode of four proposed docking models, we identified six of the myostatin residues that play an important role in the interaction with the peptide. This result provides a valuable insight into the relationship between myostatin and peptide interaction sites and may help in the design of future inhibitors.